Automatic Garbage Segregation System - Zulkifli, Muhammad Fathi Yakan; Mohamed Nasir, Noorhamizah (Evolution in Electrical and Electronic Engineering, 2021)
Recently, the recycling program was given attention by the government because the landfill area has become increasingly limited at the same time waste material also increases. This indicates that recycling attitudes among the community are still low. Recycling is important to reduce the need for raw material extraction, refining, and processing, all of which pollute the air and water. Recycling saves energy while also lowering greenhouse gas emissions, which aids in the fight against climate change. This research is to develop a dustbin that can segregate different garbage materials which are plastic, paper and aluminium automatically. The idea for this bin is to solve landfill problems or to reduce garbage disposal to landfills. This dustbin is suitable to be placed in public and a kitchen for dry waste only specific for plastic, aluminium and paper. To classify the type of garbage, there are two components used, infrared sensor and inductive proximity sensor. Besides, this dustbin also equips with ESP8266 to send notification to the owner when the garbage is near the limit or full. The segregation success rate for plastic bags, bottle plastic, newspaper, tissue paper, money envelopes and aluminium cans after 50 attempts is 100%, 96%, 96%,100%,100% and 90%. It is concluded that the objective that has been achieved is to segregation garbage automatically and evaluate the performance of the using infrared sensor and inductive proximity sensor to classified plastic, paper and aluminium. In future work, wet sensors can be added to isolate wet material like food waste. This can make this bin multipurpose and suitable to be placed in the kitchen.